Teaching Religious Moderation by Islamic Education Lecturers: Best Practices at Three Islamic Universities in Mataram City - Syahri, Akhmad; Yahya, Safaruddin; Saleh, Ali Matuq Ali (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
The study underscores the criticial role of religious moderation in preventing intolerance and radicalism among university students, particularly in Mataram city. The integration of religious moderation in the learning process has not been has been lacking, despite their crucial position in developing high-quality, balanced educational materials. This qualitative research investigates the teaching practices of religious moderation among Islamic education lecturers, employing in-depth interviews with lecturers from three Islamic universities in Mataram City. The findings reveal that religious moderation is taught using a moderate narrative approach that is integrated with other subjects. This is supported by various activity programs centered on moderation. Teaching occurs within a transformative-moderative model that aligns with academic objectives and is disseminated through social media platforms. This research highlights a significant gap in the teaching of religious moderation, both formally and informally, and emphasizes the importance of nurturing this core Islamic principle through social and religious engagement. The study recommends widespread communication of religious moderation goals through inclusive, web-based platforms to promote moderate, just, and tolerant narratives. Additionally, it calls for Islamic education lecturers to carefully design lesson plans and restructure the learning process around religious moderation.